Homogeneous groups within a heterogeneous community: Evidence from an index measuring European economic integration - Jörg König; Renate Ohr (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2012)
In the light of the current economic debt crisis within the Euro zone, the heterogeneity of EU members has becoming increasingly apparent. This heterogeneity is evident not only in some single macroeconomic variables but also in the level of economic integration with the other EU members. Despite the common use of the term European integration, neither a uniform definition nor a holistic economic approach to this concept exists. Thus, the different steps and processes of European integration are hard to quantify, thereby making it almost impossible to argue objectively whether an individual EU member state has fallen behind the general speed of European integration or whether the distance to a potential core group is undesirably large. In order to fill this gap, we have developed a composite indicator - the EU-Index - measuring the extent of European economic integration of the EU member states. The EU-Index exhibits large heterogeneities between the member states with respect to overall European economic integration and with respect to various sub-indices. By using cluster analysis, however, we find relatively homogeneous country groups within this heterogeneous community. The prevailing economic heterogeneities combined with the strong and even growing clustering of EU members may create fundamental difficulties for further integration of the European Union, and may even put existing integration steps (such as the creation of the European Monetary Union) into question. The EU-Index thus offers a unique statistically solid base for political discussions and empirical investigations, since now the degree of European economic integration is numerically tangible and can be determined individually for each country.
Keywords: C43; F15; F55; 330; European Union; economic integration; multivariate analysis.; Europäische Wirtschafts- und Währungsunion; Europäische Integration; Index; EU-Staaten